Constitutive Lck activity drives sensitivity differences between CD8+ memory T cell subsets - Moogk, Duane (J Immunol, 2016)
CD8+ T cells develop increased sensitivity following antigen experience, and differences in sensitivity exist between T cell memory subsets. How differential TCR signaling between memory subsets contributes to sensitivity differences is unclear. We show in mouse effector memory T cells (T(EM)) that more than 50% of lymphocyte-specific protein tyrosine kinase (Lck) exists in a constitutively active conformation, compared with less than 20% in central memory T cells (T(CM)). Immediately proximal to Lck signaling, we observed enhanced Zap-70 phosphorylation in T(EM) following TCR ligation compared with T(CM). Further, we observed superior cytotoxic effector function in T(EM) compared with T(CM), and provide evidence that this results from a lower probability of T(CM) reaching threshold signaling due to the decreased magnitude of TCR-proximal signaling. We provide evidence that the differences in Lck constitutive activity between CD8+ T(CM) and T(EM) are due to differential regulation by SH2 domain-containing phosphatase-1 (Shp-1) and C-terminal Src kinase (Csk), and use modeling of early TCR signaling to reveal the significance of these differences. We show that inhibition of Shp-1 results in increased constitutive Lck activity in T(CM) to levels similar to T(EM), as well as increased cytotoxic effector function in T(CM). Together, this work demonstrates a role for constitutive Lck activity in controlling antigen sensitivity, and suggests that differential activities of TCR-proximal signaling components may contribute to establishing the divergent effector properties of T(CM) and T(EM.) This work also identifies Shp-1 as a potential target to improve the cytotoxic effector functions of T(CM) for adoptive cell therapy applications.